Response of tomato growth to continuous elevated CO2 concentration under controlled environment - Akhlaq, Muhammad; Zhang, Chuan; Yan, Haofang; Ou, Mingxiong; Zhang, Wencheng; Liang, Shaowei; Ikram, Rana Muhammad Adnan (International Journal of Agricultural and Biological Engineering, 2022)
CO2 fumigation has been extensively used in greenhouses cultivation to enhance crop yield. The effects under the precise level of elevated CO2 (e[CO2]) on crop morphology, yield, and fruit quality remain largely elusive yet. To explore the response of plant growth to the continuous RCPs (Representative Concentration Pathways) projected CO2 concentration [CO2], tomato (Hezuo 908) plants were grown under ambient CO2 (a[CO2], 462 µmol/mol) and e[CO2] (550, 700, 850 and 1000 µmol/mol): named as EC550, EC700, EC850, and EC1000, respectively, under uniform environmental condition for two planting seasons. Collective growth of tomato plants (plant height, stem diameter, and leaf area index) was significantly enhanced under EC700 and showed a slightly negative response under EC850. The optimum yield was stimulated under EC700 by 74.05% and 55.91%, while maximum total dry weight (DWt) was enhanced under EC1000 by 58.23% and 39.78% during autumn-winter and spring-summer planting seasons, respectively, as compared to a[CO2]. The greatest yield and least DWt stimulated under EC700 for both seasons indicated that EC700 improved the ability of the tomato plants to translocate carbohydrates to fruits. Optimum water use efficiency related to yield (WUEy) was enhanced by 55.91-210.87% under EC700 compared to a[CO2]. The titratable acid (TA) was improved by 19.94% (EC700), 29.17% (EC850), and 97.92% (EC1000), and the lycopene (Lp) was increased by 2.22% (EC700) and reduced by 2.28% (EC1000). Thus, the overall optimum impact on tomato growth was explored under EC700. Super e[CO2] did not positively influence the tomato growth process and yield under adequate water and fertilizer conditions. The present study results are beneficial for greenhouse crop production and might be used as a reference to validate the climate change influence modeling. Keywords: elevated CO2, tomato plant, yield, water use efficiency, fruit quality DOI: 10.25165/j.ijabe.20221506.7418 Citation: Akhlaq M, Zhang C, Yan H F, Ou M X, Zhang W C, Liang S W, et al. Response of tomato growth to continuous elevated CO2 concentration under controlled environment. Int J Agric & Biol Eng, 2022; 15(6): 51–59.